The Effect of Entrepreneurial and Digital Literacy on Entrepreneurial Intention of High School Student in Bandar Lampung - Emilia, Putri; Paramitasari, Niken (Proceeding International Conference on Information Technology and Business, 2023)
The purpose of this study was to examine the effect of the relationship between entrepreneurial literacy and digital literacy on entrepreneurshipintention of public high school- SMA Negeri 15 Bandar Lampung students. This research is quantitative and the research data used is primary data. The population of XII grade students of SMA Negeri 15 Bandar Lampung and the sample to be studied was 90 respondents. The analytical tool used is multiple linear regression and data collection is done through distributing questionnaires with a Likert scale. The data testing technique uses validity test, reliability test and hypothesis testing using SmartPLS 4.0 software.Â Keywordsâ€”entreprenerial literacy, digital literacy,entrepreneurialintentionÂ